The media handbook : a complete guide to advertising media selection, planning, research, and buying - Katz, Helen E. (Routledge, 2019)
"The Media Handbook provides a practical introduction to the advertising, media planning, and buying processes. Emphasizing basic calculations and the practical realities of offering alternatives and evaluating the plan, this seventh edition includes updated statistics and coverage of social media, automation, and the continuing digitization of media. It covers over-the-top television, programmatic TV, digital advertising, and the automation of buying across all media. Author Helen Katz provides a continued focus on how planning and buying tie back to the strategic aims of the brand and the client, keeping practitioners and students up to date with current industry examples and practices. The companion website [insert CW link] to the book includes resources for both students and instructors. Students have access to flashcards to test themselves on main concepts, a list of key media associations, and template flowchart and formulas. Instructors can find lecture slides and sample test questions to assist in their course preparation. Helen Katz is Senior Vice President and Global Research Director for Publicis Media. She has an extensive professional background in media research and has taught advertising and media planning at Michigan State University, DePaul University, and the University of Illinois"--